Building public libraries for teens through community engagement: A case study of a public library in South Korea - Park, Ok Nam; Oh, Euikyung (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2022)
This study investigates essential elements of public libraries for teens. Based on the community engagement model, this study adopted a case study approach with a regional central library in Seoul, South Korea. Data were collected using interviews, surveys, and meetings with the local council. Analysis of the survey with 180 teens and 60 parents was performed. Interviews with 9 teens and 10 parents and 3 local council meetings were analyzed. The study suggests improvements in services for teens in Korean public libraries. The study shows that libraries should go beyond being a space for reading and studying to become a center of connected learning.